Measuring Social Change of Migrant Family - Kuntari, Sri (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The research on measuring social welfare of migrant families is to describe social change in migrants familie structure. Methodologically, the approach used is qualitative-descriptive. Research location ditermined purposively in Sukabumi Regency, West Java Province, based on cosideration that in this regency many migrant workers go abroad, especially women working in informal sector. Subjects in this research are migrant worker women, chosen purposively, based on criteria they ever worked or are on leave status and will work back abroad. Data are gathered through interview and documentary analysis, and analyzed through qualitative-descriptive technique. The research finds that the decession of working abroad as migrant workers causes basic change in family lives to be better. The change caused by remintant contribution from working abroad, families are able enhance life quality, both on their children education and economicsocial improvement. But behind its positive change there is negative change, namely the cofusing of family member functions, between husbands and wives during they are abroad. It is recommended it should be set an integrated services unit, untited from related agencies to identify problems and needs of social services to ex-migrant workers, also it should be set local group work and communication forum for ex-migrant workers under supervision and guidance of related agencies.